Study on the Nature of Science (NOS) in Science Education Since 1895-2022: Bibliometric Analysis - Supriyadi Supriyadi; Andi Suhandi; Achmad Samsudin (CV. Dharma Samakta Edukhatulistiwa, 2023)
The purpose of this overview is to map the studies focused on the nature of science in the scientific Scopus journal. The nature of science (NOS) and its impact on pedagogical learning and science education have become central themes of education and research. The Study methodology used in this study is bibliometrics utilising VOS viewer. Specifically, research results analysis and coward analysis were carried out. The term NOS has ever been analyzed in the Scopus database. A total of 2756 papers were analyzed consisting of 2048 articles, 202 conference articles, 56 books, 263 book chapters, and 187 other papers were analyzed. The results report that studies in the field of education of NOS more increased and have continued uninterruptedly up to the present day, even though interest generated in the scientific community has been irregular. It can be concluded that NOS studies have not had an established and robust line of research over time, this study can be observed that the trends in this aspect are focused on science education.